1979
DOI: 10.1002/bjs.1800660704
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytomas in 72 patients: Clinical and diagnostic features, treatment and long term results

Abstract: SUMMARY Phaeochromocytomas were diagnosed in 72 patients in Hammersmith, Beljiast and Newcastle between 1955 and 1976. Fourteen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
8

Year Published

1982
1982
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(79 citation statements)
references
References 27 publications
6
64
1
8
Order By: Relevance
“…We found that the incidence of malignant pheochromocytomas among 152 patients with pheochromocytomas was 11.2%, in good agreement with the 8% to 12.5% previously reported [7][8][9][10][11]. We also found that the 5-year survival rate of our patients with malignant pheochromocytoma was 11.8%, which was thus somewhat lower than the 20% previously reported [12].…”
Section: Discussionsupporting
confidence: 89%
“…We found that the incidence of malignant pheochromocytomas among 152 patients with pheochromocytomas was 11.2%, in good agreement with the 8% to 12.5% previously reported [7][8][9][10][11]. We also found that the 5-year survival rate of our patients with malignant pheochromocytoma was 11.8%, which was thus somewhat lower than the 20% previously reported [12].…”
Section: Discussionsupporting
confidence: 89%
“…These include rhabdomyosarcoma and phaeochromocytoma (Modlin et al, 1979;Hartley et al, 1988). We encountered one case of rhabdomyosarcoma and one case of paraganglioma.…”
Section: Discussionmentioning
confidence: 99%
“…The most rigorous definition of malignancy is that which requires that metastases should be present at a site where chromaffin tissue is not otherwise found, thus excluding the possibility of misclassifying multifocal primary lesions as metastases. The prognosis from a variety of reports of malignant phaeochromocytomas appears highly variable (Palmieri e f d., James et al, 1972;Mahoney & Harrison, 1977;Modlin et al, 1979).…”
Section: B Sliapiro Etmentioning
confidence: 99%